2023
DOI: 10.1515/reveh-2022-0245
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exposure to heavy metals on the increased health risk and carcinogenicity of urinary tract (kidney and bladder)

Abstract: In today’s society, with the continuous development of manufacturing industries and factories related to chemicals, the amount of heavy metals in the inhaled air of humans, water and even food consumption has increased dramatically. The aim of this study was investigation of relationship between exposure to heavy metals on the increased carcinogenicity risk of kidney and bladder. Databases used to for searched were the Springer, Google Scholar, Web of Science, Science Direct (Scopus) and PubMed. At the end aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In recent years, intensive metal mining and smelting activities have resulted in significant heavy metal contamination in farmland soils surrounding mining areas. Pollution of these farmland soils poses a serious threat to the soil ecosystem due to its high toxicity, mobility, and non-degradation and its transfer to the food chain through uptake by crops, which induces diseases such as bone pain and kidney failure [1][2][3]. Consequently, research into remediation techniques for heavy-metal-contaminated soils in mining areas has garnered widespread attention from scholars worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, intensive metal mining and smelting activities have resulted in significant heavy metal contamination in farmland soils surrounding mining areas. Pollution of these farmland soils poses a serious threat to the soil ecosystem due to its high toxicity, mobility, and non-degradation and its transfer to the food chain through uptake by crops, which induces diseases such as bone pain and kidney failure [1][2][3]. Consequently, research into remediation techniques for heavy-metal-contaminated soils in mining areas has garnered widespread attention from scholars worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that green tea may provide significant health benefits. Polyphenols contribute to enhancing health and serve as therapeutic agents for kidney diseases, preventing the onset of degenerative diseases such as cancer, cardiovascular diseases, neurodegenerative disorders, and metabolic disturbances [14]. In addition to polyphenols, tea also contains various chemical elements such as tannins, alkaloids like caffeine and theobromine, polysaccharides like D-rhamnose, L-arabinose, and minerals like sodium, magnesium, potassium, phosphorus, titanium, zinc, and iron [7].…”
mentioning
confidence: 99%